Evaluation of diastole by echocardiography for detecting early cardiac dysfunction: an outcome study - Tatiana Kuznetsova; Nicholas Cauwenberghs; František Sabovčik; Yukari Kobayashi; Francois Haddad (ESC Heart Failure, 2022)
Abstract Aims Timely detection of subclinical left ventricular diastolic dysfunction (LVDDF) is of importance for precise risk stratification of asymptomatic subjects. Here, we evaluated the prevalence of LVDDF and its prognostic significance in the general population using two grading approaches: the 2016 ASE/EACVI recommendations and population‐derived, age‐specific criteria. Methods and results We randomly recruited 1407 community‐dwelling participants (mean age, 51.2 years; 51.1% women; 53.5% with cardiovascular risk factors). We measured left heart dimensions, strain, tricuspid regurgitation, transmitral blood flow, and mitral annular tissue velocities using conventional echocardiography and Doppler imaging. We utilized these measurements to grade of LVDDF according to the 2016 recommendations and population‐derived, age‐specific approach. According to the 2016 recommendations, 26 subjects (1.85%) were classified as having the advanced stage (Grade 2), whereas in 109 participants (7.75%) diastolic function was indeterminate. When applying the population‐derived criteria, the prevalence of advanced LVDDF was 17.9% (n = 252). During the follow‐up period (8.4 years), 100 participants experienced adverse cardiac events. After full adjustment, we did not observe any significant differences in the risk of events between subjects with indeterminate or any grade of LVDDF and subjects with normal diastolic function when classified according to the 2016 recommendation (P ≥ 0.25). In contrast, the adjusted risks of adverse cardiac events (HR = 1.28; P = 0.0045) were significantly elevated in participants with LVDDF when classified according to the population‐derived criteria. Conclusions Our study underscored the importance of considering age‐ and population‐derived thresholds in LVDDF grading in subjects at high cardiovascular risk which led to a better risk stratification and outcome prediction.